Elevated CO2 concentrations alleviate the inhibitory effect of drought on physiology and growth of cassava plants - Cruz, J.L.; Alves, A.A.C.; LeCain, D.R.; Ellis, David; Morgan, J.A. (Elsevier, 2016)
Due to the rise in anthropogenic greenhouse gas concentrations, the earth's climate is expected to change, with precipitation being reduced in some areas resulting in growth-limiting drought and, as a consequence, reduced plant productivity. We investigated the physiological and growth responses of cassava (Manihot esculenta Crantz) to approximate present-day ambient (390 µL L-1) and elevated (750 µL L-1) atmospheric CO2 concentrations under well-watered and water deficit conditions, aiming at understanding how cassava would face those problems. Water deficits led to reductions in the Leaf Elongation Rate of plants grown at ambient as well as CO2-enriched concentrations. However, plants grown at 750 µL L-1 of CO2 maintained leaf growth two days longer than plants grown at 390 µL L-1. Three Days After Withholding Water (DAWW), photosynthesis and stomatal conductance were reduced in plants grown under ambient CO2, while in plants under an elevated CO2 concentration, these physiological functions remained similar to that of control plants grown under good water availability. Five DAWW plants grown with 750 µL L-1 continued to have enhanced gas exchange compared with plants grown under 390 µL L-1. Under drought stress, the instantaneous transpiration efficiency was always greatest for plants grown under elevated CO2. The positive response of elevated CO2 levels on total dry mass was 61% in the water-stressed plants and only 20% for the plants grown under good water availability. Stomatal limitation was an important factor reducing CO2 assimilation in cassava growing under drought conditions.